Pharmacokinetics and Pharmacodynamics of Lanoteplase (n-PA) - Nordt, Thomas K.; Moser, Martin; Kohler, Benedikt; Kübler, Wolfgang; Bode, Christoph (Thrombosis and Haemostasis, 1999)
In acute myocardial infarction rapid, complete, and sustained reperfusion of the infarct-related coronary artery is the most important therapeutic principle. Lanoteplase or n-PA, a third-generation plasminogen activator consisting of a deletion and point mutant of tissue-type plasminogen activator (t-PA), is a promising agent to appraoch this therapeutic goal. The molecule exhibits an increased plasma half-life allowing single-bolus administration. In this article, after characterizing the n-PA molecule, the currently available pharmacokinetic and pharmacodynamic data including the results of the InTIME study are reviewed.
Keywords: Myocardial infarction; reperfusion; thrombolysis; plasminogen; activator